2013
DOI: 10.4102/phcfm.v5i1.442
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of maternal mortality using verbal autopsy at Sokoto, North-Western Nigeria

Abstract: BackgroundMaternal mortality in developing countries is higher than that in developed countries. There are few published articles on the factors associated with maternal deaths in northern Nigeria.ObjectivesThe objective of this study was to identify the medical causes and factors associated with maternal mortality in Sokoto, northern Nigeria.MethodA verbal autopsy questionnaire was used to interview close relatives of women within the reproductive age group who had died of pregnancy-related complications in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
3
1
0
Order By: Relevance
“…These are all causes which can be reduced by effective emergency antenatal care and skilled care at birth to prevent, detect and manage mild complications, and obstetric care. However, our results were consistent with other studies, for example in Sokoto, Western Nigeria [ 22 ] which reported 48.3% of maternal deaths due to postpartum haemorrhage and a previous study from Tigray that reported 39% of maternal deaths due to haemorrhage [ 23 ]. Pregnancy–induced hypertension has also been reported as a major cause of maternal death in other studies, for example 19% in Nigeria [ 22 ], 28% in Haiti [ 24 ] and 19% in Tigray [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These are all causes which can be reduced by effective emergency antenatal care and skilled care at birth to prevent, detect and manage mild complications, and obstetric care. However, our results were consistent with other studies, for example in Sokoto, Western Nigeria [ 22 ] which reported 48.3% of maternal deaths due to postpartum haemorrhage and a previous study from Tigray that reported 39% of maternal deaths due to haemorrhage [ 23 ]. Pregnancy–induced hypertension has also been reported as a major cause of maternal death in other studies, for example 19% in Nigeria [ 22 ], 28% in Haiti [ 24 ] and 19% in Tigray [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, our results were consistent with other studies, for example in Sokoto, Western Nigeria [ 22 ] which reported 48.3% of maternal deaths due to postpartum haemorrhage and a previous study from Tigray that reported 39% of maternal deaths due to haemorrhage [ 23 ]. Pregnancy–induced hypertension has also been reported as a major cause of maternal death in other studies, for example 19% in Nigeria [ 22 ], 28% in Haiti [ 24 ] and 19% in Tigray [ 11 ]. This might reflect a lack of access to anticonvulsant drugs like magnesium sulphate, either because of stock issues or lack of appropriate use, assuming that women get to facilities in the first place.…”
Section: Discussionsupporting
confidence: 93%
“…The low utilization of MHS in the North West and North East zones observed in our study is consistent with other reports that indicated the North West and North East zones have the highest maternal and perinatal fetal deaths due to high prevalence of high risk pregnancies such as pregnant teenagers, pregnancies among women greater than 35 years, short interval between births, and grand multipara (Doctor et al, 2011;Fapohunda & Orobaron, 2014;Fawole et al, 2012;Garba & Umar, 2013). These high-risk pregnancies were similarly reported in areas with low utilization of MHS in other parts of Nigeria (Adeoye, Onayade, & Fatusi, 2013) and developing countries (UNICEF, 2012;Yego, D'Este, Byles, Williams, & Nyongesa, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…This could have led to the late identification of complicated pregnancies and could be partially responsible for Nigeria being among the top 11 countries with the highest maternal mortality rates in the world (WHO et al, 2010). Furthermore, only 34% of deliveries are supervised by trained personnel (WHO, 2013), and many women come in with life-threatening conditions (Fawole et al, 2012;Garba & Umar, 2013). This means that nearly two thirds of all births were conducted in homes or in health facilities that are not well equipped and are not supported by individuals with sufficient technical competence.…”
Section: Introductionmentioning
confidence: 99%
“…VA surveys have been implemented in LMICs such as India, Brazil, Bangladesh, and Sri Lanka (Serina et al 2015). A number of verbal and social autopsy (VASA) surveys have also been implemented in Nigeria, Niger, Cameroon, and Malawi (Garba and Umar 2013;Koffi et al 2016;Lasisi et al 2018). A nationally representative VASA survey was conducted in Nigeria in 2014 to determine COD amongst children under 5 (U5) as a follow-up to the 2013 National Demographic and Health Survey (NDHS) (Koffi et al 2017).…”
Section: Verbal Autopsy As a Solution To Mortality Data Challenges In...mentioning
confidence: 99%